UPAYA MENINGKATKAN KECERDASAN SPIRITUAL PESERTA DIDIK MELALUI MANAJEMEN PESERTA DIDIK - Uswatun Hasanah; Muhammad Fadillah; Khizanaturrohmah Nur Maziyah; Mileni Apriliana; Rizqiana Azizah Saraswati; Nurul Arfinanti (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2020)
The main problem in this research is how well the management of students pursued by Madrasah Aliyah Negeri III Sleman in order to improve the spiritual intelligence of their students is. In accordance with said main problem, this study aims to describe efforts in improving the quality of spiritual intelligence of students through student management in Madrasah Aliyah Negeri III Sleman. The research method used is descriptive method through qualitative research approach. The results of the research are as follows (1) student management planning and spiritual intelligence in Madrasah Aliyah Negeri III Sleman; (2) placement of student management in Madrasah Aliyah Negeri III Sleman to realize spiritual intelligence (3) development activities in realizing spiritual intelligence. Keywords: Spiritual Intelligence, Students, Student Management